MENINGKATKAN KETERAMPILAN KOMUNIKASI INTERPERSONAL PADA SISWA YANG MEMILIKI KECENDERUNGAN ADIKSI SITUS JEJARING SOSIAL. - Dewi, Vivit Puspita (Universitas Pendidikan Indonesia, 2018)
Abstract:. The purpose of the research is to find out and prove empirically about the effectiveness of sosiodrama techniques to improve interpersonal communication skills in students. The main problem of the research was